A Weighted Average of Multiple Inversions of Rayleigh Wave Dispersion Curve Using Particle Swarm Optimization for Geotechnical Site Characterization - Jamhir Safani; Rezki Wirawan; Al Rubaiyn Rubaiyn; Mohd Nawawi; Toshifumi Matsuoka (Department of Physics, Sebelas Maret University, 2023)
Shear wave velocity is an important parameter in geotechnical engineering for studying liquefaction, finding bedrock for the basement of a building, and figuring out the presence of subsurface cavities. This study aims to develop and evaluate the accuracy of the multiple inversions by the Particle Swarm Optimization (MI-PSO) algorithm with a weighted average solution. This algorithm is applied to Rayleigh wave dispersion data for geotechnical site characterization. Two synthetic models, the HVL model and the complex model (i.e., a combination of models with LVL and HVL characteristics), are used to conduct algorithm tests. These synthetic models replicate subsurface characteristics that are frequently encountered in geotechnical cases. Synthetic data tests show that the MI-PSO algorithm with a weighted average solution works excellently. The MI-PSO technique with a weighted average solution resolves the model better than the conventional average solution. When applied to two field data sets, the MI-PSO algorithm with a weighted average solution can delineate target models that are consistent with the qualitative interpretation based on the observed dispersion curve characteristics.